Microstructure Evolution and Shear Strength of Tin-Indium-xCu/Cu Joints - Duy Le Han; Yu-An Shen; Fupeng Huo; Hiroshi Nishikawa (Metals, 2021)
The low melting temperature In-48Sn alloy is a promising candidate for flexible devices. However, the joint strength of the In-48Sn alloy on the Cu substrate was low due to the rapid diffusion of Cu into the In-rich alloy. In this study, the effect of the addition of xCu (x = 2.0 and 8.0 wt.%) on wettability, interfacial reaction, and mechanical strength of the In-Sn-xCu/Cu joint is analyzed. The results demonstrate that both the In-48Sn and In-Sn-xCu alloys exhibit good wettability on the Cu substrate and that the contact angle increases with an increase in the Cu content. Furthermore, fine grains are observed in the alloy matrix of the In-Sn-xCu/Cu joint and the interfacial intermetallic compound (IMC) comprising the Cu-rich Cu6(In,Sn)5 near the Cu substrate and the Cu-deficient Cu(In,Sn)2 near the solder side. The In-Sn-2.0Cu/Cu joint with fine microstructure and a small amount of IMC in the alloy matrix shows the highest average shear strength of 16.5 MPa. Although the In-Sn-8.0Cu/Cu joint also exhibits fine grains, the presence of large number of voids and rough interfacial IMC layer causes the formation of additional stress concentration points, thereby reducing the average shear strength of the joint.